2020
DOI: 10.1177/0883911520911660
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, biocompatibility, and physicochemical properties of novel adhesive methacrylate dental monomers

Abstract: For the advancement of Class V restoratives, our goal was to evaluate the physicochemical and mechanical properties, antimicrobial functionality, and cytotoxic potential of novel antimicrobial copolymers. 5-Carboxy-N-(2-(methacryloyloxy)ethyl)-N,N-dimethylpentan-1-aminium bromide (AMadh1) and 10-carboxy-N-(2-(methacryloyloxy)ethyl)-N,N-dimethyldecan-1-aminium bromide (AMadh2) were incorporated into light-curable urethane dimethacrylate, polyethylene glycol–extended urethane dimethacrylate, ethyl 2-(hydroxymeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Testing of Streptococcus mutans UA-159 (ATCC ® 700610) planktonic forms was according to described methods [47,58]. Briefly, bacterial cultures with an optical density of 1.2-1.3 at 600 nm (Unico ® 1200 Spectrophotometer, United Products & Instruments, Inc., Dayton, NJ, USA) were diluted and seeded onto copolymer disks at a density of~3 × 10 7 CFU/disk.…”
Section: Mechanical Properties Of Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing of Streptococcus mutans UA-159 (ATCC ® 700610) planktonic forms was according to described methods [47,58]. Briefly, bacterial cultures with an optical density of 1.2-1.3 at 600 nm (Unico ® 1200 Spectrophotometer, United Products & Instruments, Inc., Dayton, NJ, USA) were diluted and seeded onto copolymer disks at a density of~3 × 10 7 CFU/disk.…”
Section: Mechanical Properties Of Copolymersmentioning
confidence: 99%
“…A bioluminescent S. mutans strain JM 10 (derivative of wild type UA159 [59] was used to assess the AM properties of AM sil s . Methods of the real-time bioluminescence assay were as described [41,58].…”
Section: Biofilmmentioning
confidence: 99%
“…However, the antimicrobial efficacy–structure relationships are not strictly linear. For instance, the longer chain length of novel adhesive methacrylate dental monomers had a less marked effect on reducing S. mutans biofilms [ 20 ]. Furthermore, when drawing conclusions about chain length, it is important to consider that antimicrobial functionality is also affected by molecular mass, spacer rigidity, hydrophobicity, charge density, and charge distribution [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when drawing conclusions about chain length, it is important to consider that antimicrobial functionality is also affected by molecular mass, spacer rigidity, hydrophobicity, charge density, and charge distribution [ 21 , 22 ]. Since the first Imazato and coworkers’ QAC resin manuscript, advances have been made in synthesizing QAC monomers with dual functionality, such as increased shear bond strength [ 20 , 23 , 24 ] and silane-coupling capabilities [ 25 , 26 , 27 ]. Similarly, other antimicrobial approaches have been studied in dentistry, including metallic nanoparticles with inherent bactericidal properties [ 28 ] and are not discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is reported that urethane dimethacrylate considered as a favorable resin to attain uniform distribution of calcium phosphate based fillers. 9 Silane is the most common coupling agent used to immobilize HA particles and connect organic and inorganic phases in the resin matrix. During the silanization process, several factors can affect coupling efficiency such as the nature of solvent, pH, and concentration of the coupling agent.…”
Section: Introductionmentioning
confidence: 99%